Capacidad de regeneración de Dugesia tigrina expuesta a diferentes concentraciones de Pelargonium roseum - Herrera Avila, Estefania Yunet (2018)
In the present work the effect of 4 concentrations of Pelargonium roseum (0%, 0.1%, 0.2% and 0.3%) on the regeneration capacity of Dugesia tigrina was determined, for which, each copy of Dugesia was made, a longitudinal section fragments were obtained (right and left), cross section obtaining the fragments (upper and lower) and double cross cutting obtaining the fragments (cephalic, middle and caudal), to then be exposed to treatments consisting of different concentrations of Pelargonium roseum, the blastema formation time and the complete regeneration time of the Dugesia tigrina individual were measured. When performing the reading under an optical microscope, we showed that treatment 4 (0.3% of P. roseum) is the one that promoted the shortest time for visible formation of the blastema with (85.26 hours) and treatment 4 (0.3% of P. roseum). ) promoted a shorter time for the total formation of the individual (173.83 hours). The analysis of variance evidenced the significant presence between treatments and the comparison test of means established the conformation of different homogeneous groups.